CABLAKA SEBAGAI INTI MODEL KARAKTER MANUSIA BANYUMAS - Priyadi, Sugeng (Diksi, 2015)
Cablaka is the central of model care of the Banyumas man character. The character perceived by the outers that Banyumas man have no regard on ethics, they are vulgars, or be even they behave unwell because they rude their attitude can hurt others. Moreover, they speak many vulgar words. Cablaka has internalized into a whole circle of Banyumas man model through their egalitary, freedom, and frankliness impressed to be a vulgarity. Keywords : cablaka, model care, character, ethics, vulgar words, egalitary, freedom, and frankliness.